Carbon Dioxide and the Carbamate Post-Translational Modification - Blake, Lynsay I.; Cann, Martin J. (Frontiers in Molecular Biosciences, 2022)
Carbon dioxide is essential for life. It is at the beginning of every life process as a substrate of photosynthesis. It is at the end of every life process as the product of post-mortem decay. Therefore, it is not surprising that this gas regulates such diverse processes as cellular chemical reactions, transport, maintenance of the cellular environment, and behaviour. Carbon dioxide is a strategically important research target relevant to crop responses to environmental change, insect vector-borne disease and public health. However, we know little of the direct interactions of carbon dioxide with the cell. The carbamate post-translational modification, mediated by the nucleophilic attack by carbon dioxide on N-terminal α-amino groups or the lysine ɛ-amino groups, is one mechanism by which carbon dioxide might alter protein function to form part of a sensing and signalling mechanism. We detail known protein carbamates, including the history of their discovery. Further, we describe recent studies on new techniques to isolate this problematic post-translational modification.